Portunus anceps ... - In, First Published (Zenodo, 2022)
Portunus anceps (Saussure, 1857) (Fig. 29A–F) Lupea anceps Saussure, 1857: 502 [Type locality: Cuba]. Lupea anceps Saussure, 1858: 434 (18) [see Hollier, 2018]. Trindade and Martin Vaz specimens. 1 male (MZUSP 33826), Brazil, off Espírito Santo, Trindade Island, Praia do Lixo, 20°31’29.8’S, 29°19’43.9”W, J.B. Mendonça coll., 25.x.2014, 13.7 m. 1 juvenile (MZUSP 40185), ibidem, J.B. Mendonça coll., 22.xi.2017, 12.7 m. 1 female (MZUSP 40178), ibidem, Ponta Norte, 20°29’18.7”S, 29°20’18.3”W, J.B. Mendonça coll., 27.xi.2017, 10.7 m. 1 male (MZUSP 40184), ibidem, Enseada das Orelhas, 20°29’40.2”S, 29°20’32.9”W, J.B. Mendonça coll., 27.xi.2017, 10.3 m. 2 juveniles (MZUSP 40181), ibidem, Enseada dos Portugueses, R /V “Marion Dufresne”, TAAF MD55/Brésil Expedition coll., 22.v.1987, vacuum suction sampler, 10 m. 3 juveniles (MZUSP 41464), ibidem, off Trindade Island, stn 36 DC61, 20°29’S, 29°18’W, 22.v.1987, 63 m. 1 juvenile (MZUSP 40183), ibidem, Ponta da Calheta, 20°30’18.72S, 29°18’31.6”W, J.B. Mendonça coll., ... : Published as part of In, First Published, 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 on page 56, DOI: 10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155 ...